An enzyme-linked immunosorbent-assay test for hepatitis B surface antigen. - Vandervelde, E M (1977)
A new commercial test for hepatis B surface antigen based on an enzyme-linked immunosorbent-assay system was evaluated and compared with other tests already available. It was of comparable sensitivity to the radioimmunoassay test but required less expensive equipment (in terms of both outlay and upkeep) and did not use radioisotopes; the reagents were more stable.